An evaluation of the General Bathymetric Chart of the Ocean in shoreline-crossing geomorphometric investigations of volcanic islands - Klein, Elisa; Hadré, Emma; Krastel, Sebastian; Urlaub, Morelia (Frontiers in Marine Science, 2023)
Digital elevation models (DEMs) are crucial in natural hazard assessments, as they often present the only comprehensive information. While satellites deliver remote sensing information of the land surface of up to 2m resolution, only 25% of the seafloor is mapped with a minimum resolution of 400m. The acquisition of high-resolution bathymetry requires hydroacoustic surveys by research vessels or autonomous vehicles, which is time-consuming and expensive. Predicted bathymetry from satellite altimetry, on the other hand, is widely available but has a significantly lower spatial resolution and high uncertainties in elevation, especially in shallow waters. The research on volcanic islands as a source of both volcanic as well as marine hazards, such as tsunamis, is greatly limited by the lack of high-resolution bathymetry.Here we find that using the comprehensive bathymetric data of the General Bathymetric Chart of the Ocean (GEBCO) in a geomorphometric study on volcanic islands produces mostly robust parameters, including in areas, where indirect measurements from satellite altimetry is the only available information. We conclude this from a comparison of 24 parameters of 47 volcanic islands derived from a) GEBCO and b) high-resolution (<250m), ship-based bathymetry. Out of 24 parameters tested, 20 show <±2.5% median deviation, and quartiles <±10%. Parameters describing the size of a volcanic island are the most robust and slope parameters show the greatest deviations. With this benchmark, we will be able to increase geomorphometric investigations to volcanic islands where little or no high-resolution bathymetry data is available.